Anselm on freedom - Rogers, Katherin A. (Oxford : Oxford University Press, 2008)
Can human beings be free and responsible if there is an all-powerful God? Anselm of Canterbury offers viable answers to questions which have plagued religious people for at least 2000 years. Katherin Rogers examines Anselm's reconciliation of human free will and divine omnipotence in the context of philosophical debates.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Anselm, -- Saint, Archbishop of Canterbury, -- 1033-1109.; Liberty